Development of E-book “FLASHBACK SEJARAH SASTRA” as a Supporting Source of Literaturgeschichte Course of German Literature Universitas Negeri Malang - Ade Putri Maysari; Deddy Kurniawan (Universitas Negeri Malang, 2022)
This research and development aim to test the validity of the feasibility of the e-book